The 'good death' and reduced capacity: a literature review. (2nd October 2018) - Read, Simon; MacBride-Stewart, Sara
Abstract: Research effort into what a 'good death' entails has generally concentrated on six themes: pain and symptom management; clear decision-making; preparation for death; completion; contributing to others; and affirmation of the whole person. This review explores these themes, specifically examining their applicability to those who lack mental capacity to make their own decisions. Some appear more relevant than others, with clear decision-making and affirmation of personhood predicating issues related to reduced capacity. Largely, however, the literature on a 'good death' builds on an underlying assumption that the dying patient is cognisant and capable of rationalising their death. Those instances where mental capacity is acknowledged within the model have been met by criticism from numerous authors. Factors such as the subjectivity of substitute decision-makers and the complexity associated with medico-legal interpretations of current legislation help to highlight deficiencies in the application of principles of a 'good death' in practice. Further specific consideration is required on how to achieve a 'good death' for those with reduced capacity.